A Comparative analysis of global competences within the framework of internationalized curricula - Pablo Beneitone; Maria Yarosh (Universidad de Deusto, 2021)
An agreement seems to exist that graduates must be equipped with competences required to act successfully and appropriately in a global context. Many authors have proposed lists of competences that could form part of such a graduate profile which must be taken into account when designing internationalized curricula. However, merely listing of a competence does not guarantee that students develop it to the level expected by society. The present article reports on a meta-study based on eight Tuning studies. This meta-study compared the findings across the eight Tuning studies in terms of the different stakeholder groups' ratings of importance and achievement of 11 global competences - generic competences valued by over 71,000 graduates, employers, students and academics in more than 100 countries and across four continents (Europe, Latin America, Africa and Asia). The contribution of the meta-study presented consists in offering a possibility to identify commonalities and differences among the perceptions of the four key stakeholder groups, not only across all the individual studies but also at the level of the four continents - something never accomplished until the present date. In addition, it will help identify the competences that might require particular attention of curriculum designers and teaching teams for students to develop these competences to the level perceived as optimal in different regions of the world. Future research questions are identified with the aim to enrich and validate or fine-tune these initial findings and compensate for the limitations related to the general timeline of the 8 individual Tuning studies that the meta-study built on. Received: 31 March 2021 Accepted: 06 May 2021